Citrus Rgl (Citrus Reticulata) Farmers Satisfaction To Their Marketing Institution Services In Rejang Lebong District - emlan fauzi; Ketut Sukiyono; Muhammad Zulkarnain Yuliarso (Journal of Agri Socio Economics and Business, 2020)
The existence of RGL orange marketing institutions is very important for the development of RGL orange agribusiness from the marketing aspect. The services of a marketing agency are divided into several dimensions, each of which has service attribute items. This study aims to: (1) analyze the level of marketing institutional performance in RGL orange farming (2) analyze the level of farmer satisfaction with marketing institutional performance in RGL orange farming and (3) analyze the factors that influence the level of farmer satisfaction with marketing institutional performance in RGL orange farming in Bermani Ulu Raya District, Rejang Lebong Regency. The study was conducted in May to October 2019 in Bermani Ulu Raya District, Rejang Lebong Regency. Census data collection of 117 RGL citrus farmers. Data were analyzed with Importance Performance Analysis (IPA), Customer Satisfaction Index (CSI) and multinomial logistic regression. The results showed the marketing institutional performance was good. The quality of service that needs to be improved is the dimension of trustworthiness, assurance, direct evidence and empathy and responsiveness. The level of satisfaction of RGL citrus farmers to their marketing institutions is in the satisfied category (73.58%). The factor that significantly influences satisfaction on marketing institutions is price suitability.